Adaptation of priority research direction in agriculture to climate change in kazakhstan - Kenenbayev SB; Yesenbayeva GL (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
The negative effects of climate change in agriculture are already felt in the form of reduced yields and more frequent extreme weather events affecting both crops and livestock. It will require a significant investment in adaptation to maintain the current crop and the necessary increase in production, as the most threatened sector of the economy.